2019
DOI: 10.1111/cas.14108
|View full text |Cite
|
Sign up to set email alerts
|

Proximity proteomics identifies cancer cell membrane cis‐molecular complex as a potential cancer target

Abstract: Cancer‐specific antigens expressed in the cell membrane have been used as targets for several molecular targeted strategies in the last 20 years with remarkable success. To develop more effective cancer treatments, novel targets and strategies for targeted therapies are needed. Here, we examined the cancer cell membrane‐resident “cis‐bimolecular complex” as a possible cancer target (cis‐bimolecular cancer target: BiCAT) using proximity proteomics, a technique that has attracted attention in the last 10 years. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 57 publications
(75 reference statements)
0
20
0
Order By: Relevance
“…Western blot analysis of CD63 confirmed that EVs could be crudely purified from mouse serum by a polymer precipitation method (Figure 2A). CHL1, which is the molecule constituting LC BiCAT (Kotani et al, 2019), was also detected at higher levels in serum EVs from EML4-ALK transgenic mice (Supplementary Figure 1A). EMARS products from precipitated serum EVs (crude EVs) were detectable in CHL1 probe (+) samples, but not in EMARS probe (-) samples, indicating that EMARS reacts well with CHL1 probes and no serum factors induced non-specific EMARS reactions (Figure 2B).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Western blot analysis of CD63 confirmed that EVs could be crudely purified from mouse serum by a polymer precipitation method (Figure 2A). CHL1, which is the molecule constituting LC BiCAT (Kotani et al, 2019), was also detected at higher levels in serum EVs from EML4-ALK transgenic mice (Supplementary Figure 1A). EMARS products from precipitated serum EVs (crude EVs) were detectable in CHL1 probe (+) samples, but not in EMARS probe (-) samples, indicating that EMARS reacts well with CHL1 probes and no serum factors induced non-specific EMARS reactions (Figure 2B).…”
Section: Resultsmentioning
confidence: 99%
“…The mouse and human anti-CHL1 antibodies (AF2147 and MAB2126; R&D systems, MN) were partially reduced and bound to HRP using a peroxidase labeling kit SH (Dojindo, Kumamoto, Japan). The binding capacity of the HRP-labeled antibody was evaluated as described previously (Kotani et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations